Trends in otolaryngology consult volume at an academic institution from 2014 to 2018. Issue 5 (1st September 2020) - Sher, Erica; Nicholas, Brian
Abstract: Objective: To evaluate changes in emergency department and inpatient consult volumes of an otolaryngology service at an academic medical center from 2014 to 2018. Methods: A retrospective review of all otolaryngology consults in the electronic medical record from March 2014 through December 2018 was completed. The total number of consults was recorded to determine changes in consult volume over time. Additional parameters were analyzed including volume of weekday, night and weekend, adult, pediatric, emergency department, and inpatient consults. Results: From 1 March 2014 to 31 December 2018, a total of 8806 consults were seen by the otolaryngology service. In the first year, a total of 990 consults were seen. In the final year of the time period, a total of 2416 consults were seen. This represents a 144% increase in consults over the examined time period. Similar increasing trends were seen when consults were analyzed by weekday, night/weekend, pediatric, adult, emergency department, and inpatient consults. Conclusions: This is one of the first studies examining trends in otolaryngology consult volumes at an academic medical center in the United States. Our data show that the volume of consults has increased by 144% in a 4‐year time period, predominantly due to an increase in emergency department consultations. This study demonstrates the increasing burden of emergency department consultations on an otolaryngology service at an academic medical center and highlights a potential role for increasing and improving provider availability. Level of evidence: 4. Abstract :